LESS IS MORE: HOW TO PROPITIATE INDEPENDENT LEARNING IN A HOLISTIC CLASS THROUGH THE FRAMEWORK OF THE PEDAGOGICAL MODELS OF THE UPC - Viale Tudela, Héctor Ernesto (2007)
This article presents the design of the Math Level 0 course aligned with the Educational Model of the UPC and developed under the structure proposed by 'MATE'. The phrase 'Less is more' that gives name to this article describes a philosophical concept which is applicable to the classroom where the teacher only intervenes when it is necessary. In this context, the student has the major role.  'Less is More' requires the student accessing knowledge with enthusiasm, which will occur if the student has a major role in the teachinglearning system. The teachers are one more resource in the classroom and while the knowledge that should be acquired is important, the learning process learnt by the student on their own is paramount. It is expected in 'Less is More' that the teacher favours the learning of the students in an environment of tolerance and respect and it is demanded from the teacher to create a varied and stimulating learning experience instead of imparting knowledge in a patronizing way.